Geschichte der ladinischen Literatur Ein bio-bibliografisches Autorenkompendium von den Anfängen des ladinischen Schrifttums bis zum Literaturschaffen des frühen 21. Jahrhunderts - Videsott, Paul (d570bb8b-41c1-41d2-83cb-237ddb6c7a02, 2014)
This history of Ladin literature provides for the first time a comprehensive overview of 230 Dolomite-Ladin authors from the beginnings of Ladin literature (17th century) up to contemporary Ladin writing (2012). Each article on the authors contains a detailed biography, a complete catalog of works and a review of the oeuvre based on a representative sample of original texts, also translated into German. This new standard reference of Rhaeto-Romance Studies is completed by introductory chapters on the beginnings and the development of Ladin literature, its genres and themes, the history of research, the presence of Ladin literature in the Ladin-speaking media, the presence of Ladinia in German and Italian literature as well as a name index with as many as 3,000 entries.